Paganism and Politics: A View from Central-Eastern Europe - Strmiska, Michael F. (Pomegranate, 2018)
A conference on “Paganism and Politics” held at Masaryk University in Brno, Czech Republic in June of 2016 provided a platform for a stimulating discussion of the ways in which modern Paganism is affected by and involved with political and social issues in Central and Eastern Europe and beyond. In the following, Michael Strmiska, one of the organizers and keynote speakers of the conference, provides an overview of conference papers and several other related articles that are featured in this special section of The Pomegranate, with a further selection forthcoming in the next issue.